The Spectre and the Stage: Reading and Ethics at the Intersection of Psychoanalysis, the neo-Victorian, and the Gothic - Gildersleeve, Jessica (Australasian Journal of Victorian Studies, 2013)
A popular critical debate in recent years has concerned the significance of spectrality in neo-Victorian fiction. With reference to Freud, Derrida, and a range of neo-Victorian authors, this essay argues that the emphasis on the ways in which the past returns to haunt in the neo-Victorian permits a reading of the psychoanalytic discourse of trauma as a mode of neo-Victorian Gothic writing. By recognising the similarities between these two “genres”, we see how we might use neo-Victorian fiction as a model for developing trauma theory and understanding the ethics of representing traumatic memory and history.